Using Mehar method to change fuzzy cost of fuzzy linear model with practical application - الدوري, محمد صادق; حمدي, اسراء منذر (Journal of Economics and Administrative Sciences, 2018)
Many production companies suffers from big losses because of  high production cost and low profits for several reasons, including raw materials high prices and no taxes impose on imported goods also consumer protection law deactivation and national product and customs law, so most of consumers buy imported goods because it is characterized by modern specifications and low prices.  The production company also suffers from uncertainty in the cost, volume of production, sales, and availability of raw materials and workers number because they vary according to the seasons of the year.  I had adopted in this research fuzzy linear program model with fuzzy figures use quarter function for cooler products of AL-Hilal Industrial Company which consisting of (6) products for the year 2015, this model was resolved by transfer of fuzzy linear program problem to a normal linear programming problem according to Mehar method, and then apply one  case of sensitivity analysis which are fuzzy cost change, and has been reaching the optimal solutions for this case.  The research found that it is better to product the same number of units in all seasons and store the surplus products of the first and fourth quarters because of a lack of a demand in that period and sell them in the second and third quarters to increase demand because the production cost is low in the first and fourth quarters and increase in the second and third quarters.